Answers

2014-06-02T20:24:42+08:00
Its a special product of sum and difference. 

(2a+6b)(2a-6b) = 4a² - 36b² 

in which you just square the first term which is (2a)² = 4a²
then square the second term which is (6b)² = 36b² 

then you put negative sign between the two 
0
2014-06-02T22:30:35+08:00
FOIL; First, Outside, Inside, Last

(2a+6b)(2a-6b)\\\\First;\ 2a\times2a=4a^2\\Outside;\ 2a\times-6b=-12ab\\Inside;\ 6b\times2a=12ba\\Last;\ 6b\times-6b=-36b^2\\\\

Combine Like Terms.

-12ba+12ab=0\\\\\boxed{4a^2-36b^2}

0